Post-Transplant Lymphoproliferative Disorder in Liver Transplant Recipients: Characteristics, Management and Outcome from a Single-Centre Experience with >1000 Liver Transplantations - Khalid Mumtaz; Nabiha Faisal; Max Marquez; Alicia Healey; Leslie B Lilly; Eberhard L Renner (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: The literature regarding post-transplant lymphoproliferative disorder (PTLD) in liver transplant recipients (LTRs) is limited.